74.5k views
1 vote
Solve. 9(4h - 6) = 2( -13 - 2h)

User Wiseass
by
5.3k points

2 Answers

3 votes

Answer:

h= 7/10

Step 1: Remove the parentheses

9(4h - 6) = 2( -13 - 2h) = 36h-54= -26 -4h

Step 2: Move the terms

36h-54= -26 -4h = 36h+4= -26 + 54

Step 3: Calculate like terms

36h+4= -26 + 54 = 40h=28

Step 4: Divide both sides

40h=28 = h= 7/10

(In decimal form - h=0.7)

User Harry Steinhilber
by
5.8k points
0 votes

Answer: h= 7/10

Explanation:

9(4h - 6 ) = 2(-13 - 2h) Distribute on both sides

9(4h) + 9(-6) = 2(-13) + 2(-2h)

36h - 54 = -26 - 4h Add 4h to both sides

+4h +4h

40h - 54 = -26 Add 54 to both sides

+54 +54

40h = 28 Divide both sides by 40

h = 7/10

User Andreas Wong
by
4.8k points